ENTERPRISE RISK MANAGEMENT AND THE QUALITY OF FINANCIAL REPORTING OF NIGERIAN COMPANIES - Oghenekome Ashafoke, Tina; Joshua Aronmwan, Edosa (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2023)
Enterprise risk management has recently been gaining attention worldwide because to the global financial crisis that followed in the wake of 2008. The study evaluated the influence of enterprise risk management on the quality of financial reporting in Nigerian companies. The main objective of the study is to investigate the impact of enterprise risk management on the quality of financial reporting in selected Nigerian companies. The study employed the Ex-post facto research design. The population of the study consists of the total companies listed on the consumer goods sector of the Nigerian Stock Exchange as at December 31, 2020. The Ex-post facto research design used secondary data from the annual reports of the selected companies and covered the period 2013 to 2020. The panel least square regression analysis and correlation analysis were used to test the four research hypotheses. The study revealed that there is a significant relationship between firms’ compliance and quality of financial reporting. The result also reveals a significant relationship between firms’ reporting framework, and financial reporting quality. However, firms’ strategy and operations revealed an insignificant relationship with quality of financial reporting. The study discovered that enterprise risk management has a significant impact on the quality of financial reporting, given the F-statistic probability of 0.009266<0.05. The study recommended that firms should adopt policies that will facilitate strategies which will help them positively standout from the industry and improve the overall quality of their financial reports. Also, the efficient and proper allocation of capital resources by firms should be encouraged and proper methods employed to boost the efficiency in order to produce higher quality financial statements.